The Effect of Trapped Ball Games on Children's Basic Movement Abilities at TK Tunas Bangsa PGRI Kedaleman Kulon Kabupaten Kebumen - Meliana Dewi Suryaningsih; R Agustinus Arum Eka Nugroho (BELIA Early Childhood Education Papers, 2024)
The problem of this research is the lack of development of children's basic motor skills in TK Tunas Bangsa PGRI, Kedaleman Kulon, Kabupaten Kebumen. The aim of this research is to analyze the influence of the Trapped Ball game on children's basic movement abilities at TK Tunas Bangsa PGRI. This study uses a quantitative approach method with an experimental research design (one group pretest posttest design). Data collection through observation and documentation techniques. The data obtained in this study were obtained through primary data and secondary data. Primary data includes direct information with students, principals, class teachers, while secondary data includes supporting documents in the form of photo documentation, notes, video recordings, books, and journals or previous research. The data analysis technique uses a simple linear regression test. The results of the study showed that the trapped ball game had an effect on the basic motor skills of early childhood children. The difference between before and after being given treatment through the trapped ball game showed that the trapped ball game had an effect on the basic motor skills of children in TK Tunas Bangsa PGRI Kedaleman Kulon Kabupaten Kebumen.